ORGANIZATIONAL THEORETICAL FOUNDATIONS OF DIGITALIZATION OF PUBLIC CONTROL IN INTERNATIONAL PRACTICE - Otabek Usmanov (Scholar Express Journals, 2021)
This article is devoted to the implementation of modern forms digitalization of public control, their solutions, advanced experience of public control of developed foreign countries, public control, and further improvement of their legal foundations.The proposals and recommendations put forward in it can be used in the development of national legislation on public control, ensuring the rule of law through further implementation and digitalization of public control practices, research on scientific and theoretical aspects of public control
Keywords: Digitalization; modern forms of public control and digitalization; international experience on public control; “theories of public control